Corporate voluntary disclosure and the separation of cash flow rights from control rights. - Lee, Kin Wai. (2008)
We find that corporate voluntary disclosure is negatively associated with the separation of cash flow rights from control rights. This result is consistent with the notion that as the separation of cash flow rights from control rights increases, controlling owners have larger incentives to expropriate the wealth of minority shareholders and low corporate disclosure constitutes a mechanism to facilitate controlling owners in masking their private benefits of control. The negative association between voluntary disclosure and the separation of cash flow rights from control rights is less pronounced for firms with greater external financing needs. This result suggests that for firms with high separation of cash flow rights from control rights, those with greater external financing needs undertake higher firm-level voluntary disclosure to reduce information asymmetry. We also find that the negative association between voluntary disclosure and the separation of cash flow rights from control rights is less pronounced for firms that have a large nonmanagement shareholder. Our result supports the role of large non-management shareholder in mitigating agency problems associated with the separation of ownership and control.